Impact of SOX2 function and regulation on therapy resistance in bladder cancer - Chen, Guodong; Chen, Yan; Xu, Ruiquan; Zhang, Guoxi; Zou, Xiaofeng; Wu, Gengqing (Frontiers in Oncology, 2022)
Bladder cancer (BC) is a malignant disease with high rates of recurrence and mortality. It is mainly classified as non-muscle-invasive BC and muscle-invasive BC (MIBC). Often, MIBC is chemoresistant, which, according to cancer stem cells (CSCs) theory, is linked to the presence of bladder CSCs (BCSCs). Sex-determining region Y- (SRY) Box transcription factor 2 (SOX2), which is a molecular marker of BCSCs, is aberrantly over-expressed in chemoresistant BC cell lines. It is one of the standalone prognostic factors for BC, and it has an inherently significant function in the emergence and progression of the disease. This review first summarizes the role of SRY-related high-mobility group protein Box (SOX) family genes in BC, focusing on the SOX2 gene and its significance in BC. Second, it discusses the mechanisms relevant to the regulation of SOX2. Finally, it summarizes the signaling pathways related to SOX2 in BC, suggests current issues to be addressed, and proposes potential directions for future research to provide new insights for the treatment of BC.